Scientific and technical support of GLONASS application in agricultural production - A. A. Artyushin; I. G. Smirnov (Сельскохозяйственные машины и технологии)
Introduction of technologies of the operated farming in agricultural production will support quality hi-tech breakthrough of agrarian sector of economy and a demand of GLONASS system and means in agriculture. The main directions of GLONASS system application in the Russian agrarian and industrial complex were noted. The list of the priority technological operations demanding use of specialized firmware and GLONASS were defined. The description of the main results of research and development were received in the All-Russian Research Institute of Mechanization for Agriculture in the field of diagnostic engineering, mathematical and the software support in creation of the automated machines for precision agriculture and also regarding standard ensuring of application of technologies of the operated farming. The main directions of researches of GLONASS application in agriculture were established. In this case development of requirements to positioning accuracy, introduction of innovative technologies of the operated farming and specialized technical means and the equipment for use of GLONASS are the most actual. The research engineering program for creation of technical means of plant production in system of precision agriculture under control of GLONASS is offered. Transition to the GLONASS/GPS technologies of precision agriculture and equipment of new generation will make it possible to solve a problem of increase of agricultural products production efficiency.